A Systematic Review of Prevalence and Risk Factors of Latent Tuberculosis Infection Among Medical and Nursing Students - Ismail, Zarini; Musa, Lailatul Hazzliza; Ithnin, Muslimah; Mohamed, Nurul Azmawati; Baharom, Nizam; Ramli, Shalinawati; Pathmanathan, Siva Gowri (Malaysian Journal of Medicine and Health Sciences, 2022)
Introduction: Clinical training may expose medical and nursing students to workplace hazards comparable to those encountered by healthcare workers (HCWs). This study was designed to investigate the prevalence of latent tuberculosis infection (LTBI) and associated risk factors among medical and nursing students. Methods: Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) criteria, a systematic review was conducted utilising four electronic databases to appraise and synthesise the literature on LTBI which used the tuberculin skin test (TST) and the blood interferon-gamma release assay (IGRA). Results: Original articles published in the English language between 2010 and 2020 were included, yielding 14 relevant articles. The average prevalence of LTBI in high-burden countries was 38.2% for TST and 20.6% for the IGRA test. According to TST and IGRA findings, the average prevalence of LTBI in nations with an intermediate burden was 16.7% and 4.7 %, respectively. The average prevalence was 2.8% and 1.1% from the TST and IGRA tests for low-burden countries, respectively. A greater risk of LTBI was shown to be related with an increase in age among postgraduate medical school students, a history of Bacillus Calmette-Guerin (BCG) vaccination, origin from high-risk tuberculosis (TB) countries, increased hours of hospital exposure, a history of contact with TB cases, a high body mass index, older age group students, and a lower TB knowledge score. Conclusion: The available evidence from this review emphasised the importance of developing and implementing efficient and cost-effective TB infection-control programmes, particularly in high-burden countries and amongst students at risk.